Palliative care presentations to emergency departments in a secondary and a sub-acute hospital: A one year incidence study. (3rd September 2017) - Wong, Joanne; Gott, Merryn; Frey, Rosemary; McLay, Jessica; Jull, Andrew
Abstract : Introduction: There is growing concern that Emergency Departments (ED) are ill equipped to manage rising palliative care demand, but actual demand is unknown. The aim of this study was to estimate the annual incidence of patients with palliative care need presenting to EDs. Methods: Retrospective case review study across two New Zealand emergency departments from 1 July 2010 to 30 June 2011. We used a two-step process where (1) administrative databases were screened for patients who had presented with 12 diseases associated with palliative care need and (2) the Gold Standard Framework Prognostic Indicator Guidance (GSF PIG) criteria were applied to the clinical records of a random sample of patients meeting the disease criterion. Results: Fifty-three thousand and fifty-seven patients presented to the EDs; 4488 (8.5%) patients had diagnostic codes indicating potential palliative care need and 1024 were randomly sampled. One hundred and eighty-eight patients (18.4%, 95%CI 16.0–20.8%) from the random sample were identified as meeting GSF PIG criteria for palliative care need. The leading diseases were cancer (26.1%), COPD (26.1%) and heart failure (22.9%). Extrapolating from the estimated incidence, 826 of the 4488 patients with 12 diseases would have met GSF PIG criteria, suggesting only 1.6% of all patients presenting to ED meet GSF PIG criteria. Conclusions: The incidence of patients with actual palliative care need presenting to EDs was lower than anticipated. Further research is needed to examine for secular trends in palliative care presentations and if the incidence rates are consistent in across ED settings.